O efeito terapêutico da prática artística: a aplicação da arteterapia no serviço de Atenção Psicossocial (CAPS) em Goiânia - Franco, Guilherme Henz (2020)
This work is the final result of exploratory research about the insertion of Art Therapy in CAPS – Psychosocial Attention Centres of Goiânia. The phenomenologic methodology was applied, with bibliographic revision, semi-structured interview and observation as techniques of data production. It comprehends the conceptualization, description and history of Art Therapy (Chapter 1); the history and theoretical foundation of CAPS as a paradigm of mental health care (Chapter 2) and data analysis from interviews, through content analysis technique (Chapter 3). The research aimed to explore which therapeutic effect is attributed to Art Therapy. The author concludes that exist several effects attributed to it, among which are highlighted the following, specifically for the context of CAPS: social reinsertion, expressiveness, cognitive elaboration of one’s own desires, achievement of autonomy, self-esteem strengthening, self-comprehension, comprehension of one’s experiences and emotions, mood stabilization, civil rights and citizenship effectuation, and development of affective social relationships. The author suggests more work can be done in order to quali and quantitatively measure some of these therapeutic effects. It has been also demonstrated that despite the growth of public mental health care service on the past decades, the conception of the service in the Psychiatric Reform has lost strength. The correspondent investment evidences it, for there is no sufficient reposition of professionals, and there are lack of material, lack of own and adequate physical structure. In this sense, the number of CAPS has risen, but the necessary investment in each one does not follow. Therefore, it is important that workers and public managers reassume an effective management of the service.